Analyzing the Likely Impact of Covid-19 on Education System - 1Mukesh Kumar Meena & 2Dr. Sonlata Bargotya (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This article has covered how Covid-19 has affected the Indian educational system. Global education systems are impacted by coronavirus. In order to stop the coronavirus from spreading, schools, colleges, and universities were closed. Parents, instructors, and kids all experience challenges when schools close. Thus, one way to keep the educational system going is through distance learning. Distance learning in developing nations is hampered by a shortage of computers, internet access, and network infrastructure. Upon reopening, educational institutions devise plans to make up for lost instruction and welcome back students. Not only has this face-to-face education system in developing nations been impacted by coronavirus. The infrastructures for virtual classrooms, online learning, and broadcast education should therefore be improved in developing nations.